Surface Plasmon Resonance Biosensor Chip for Human Blood Groups Identification Assisted with Silver-Chromium-Hafnium Oxide - Purnendu Shekhar Pandey; Sanjeev Kumar Raghuwanshi; Rajesh Singh; Santosh Kumar (Magnetochemistry, 2023)
Chromium (Cr), silver (Ag) and hafnium oxide (HfO2) are used in a surface plasmon resonance (SPR)-based biosensor with an optimized design for measuring blood groups at a wavelength of 633 nm. A buffer layer was placed on the SPR active metal in this investigation to avoid oxidation and contamination of blood samples. A theoretical model based on experimental data considered the refractive index of blood samples. The BK7 prism is the optimum substrate material for blood type identification analysis using a combination of Ag and Cr as an SPR active metal. The sensor’s performance is carefully researched in terms of its angular shift and curve width to predict the design aspects that provide precise blood-group identification. The SPR dip slope, detection accuracy and figure of merit (FOM) have been investigated concerning the subsequent generation of biosensor applications.